MOHE, UMPSA strengthen strategic leadership through reform mindset - Juliana, Mohd Ali; Mohd Mukhriz, Awang; Mohd Ferdaus, Musa (UMPSA, 2026)
JERANTUT, 12 April 2026 – The Ministry of Higher Education (MOHE), in strategic collaboration with Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), successfully organised the 2026 MOHE Top Management Revitalisation Programme, themed ‘Mind Revitalisation, Action Reform’, recently.